2009
DOI: 10.1007/s10856-009-3792-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved adherence and spreading of Saos-2 cells on polypropylene surfaces achieved by surface texturing and carbon nitride coating

Abstract: The adhesion and contact guidance of human primary osteogenic sarcoma cells (Saos-2) were characterized on smooth, microstructured (MST) and micro- and nano-structured (MNST) polypropylene (PP) and on the same samples with a silicon-doped carbon nitride (C(3)N(4)-Si) coating. Injection molding was used to pattern the PP surfaces and the coating was obtained by using ultra-short pulsed laser deposition (USPLD). Surfaces were characterized using atomic force microscopy and surface energy components were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…165 Myllymaa and coworkers deposited Si-doped CN (CN-Si) on poly(propylene) (PP) disc samples via pulsed laser deposition. 166 The coating of CN-Si can significantly convert the PP surface from being hydrophobic to hydrophilic, leading to enhanced adherence of Saos-cells on PP. Hu and coworkers reported a mix of PP-grafted maleic anhydride (PP-g-MA) with g-C 3 N 4 by refluxing the mixture for 4 hours in xylene.…”
Section: Improved Properties Of Polymer Materials Via Combination Witmentioning
confidence: 99%
“…165 Myllymaa and coworkers deposited Si-doped CN (CN-Si) on poly(propylene) (PP) disc samples via pulsed laser deposition. 166 The coating of CN-Si can significantly convert the PP surface from being hydrophobic to hydrophilic, leading to enhanced adherence of Saos-cells on PP. Hu and coworkers reported a mix of PP-grafted maleic anhydride (PP-g-MA) with g-C 3 N 4 by refluxing the mixture for 4 hours in xylene.…”
Section: Improved Properties Of Polymer Materials Via Combination Witmentioning
confidence: 99%
“…Several techniques were studied to increase the low interface energy, such as the deposition of coatings [93], plasma treatment [94,95], graft polymerization [96], and injection molding [97]. Nevertheless, a precise control in the process, and subsequent surface modification remained as a major challenge.…”
Section: Polypropylene (Pp)mentioning
confidence: 99%
“…Yan et al [36] revealed that geC 3 N 4 epoly(3-hexylthiophene) composites enhanced the hydrogen generation from water under visible light. Myllymaa et al [37] demonstrated that surface hydrophilicity of PP was improved by the addition of silicon-doped carbon nitride coatings. Our previous work reported that sodium alginate/g-C 3 N 4 nanocomposite films exhibited a remarkable increase of 118.2 C in the half thermal degradation temperature while their mechanical properties were enhanced by 103% at 6.0 wt % loadings [38].…”
Section: Introductionmentioning
confidence: 99%